Sistem Informasi Cuti Kepegawaian pada Rumah Sakit Umum Daerah Kabupaten Batu Bara - Aldi Ramadani (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Personnel Leave Application Information System Application: The Personnel Leave Information System at the Batu Bara Regency Regional General Hospital is an application built for the web-based leave application process. This research was conducted on the Staff Leave Information System at the Regional General Hospital of Batu Bara Regency using research methods, namely the Observation method, Library Research, Field Research, needs analysis, system design, and system implementation. Use Case Diagram, Activity Diagram, Data Flow Diagram ( DFD), Sequence Diagram, Class Diagram. This application was built using software, namely the PHP programming language, HTML, CodeIgniter, Composer database used by MySQL. The application built operates on the Windows Operating System. The WEB-based Application for the Information System for Applying for Employee Leave at the Batu Bara Regency Regional General Hospital has helped the Batu Bara Regency Regional General Hospital in registering and informing employee leave applications quickly and accurately, and can also provide information to employees to find out whether the leave process has been approved or not. approved.